(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
his paper discusses the process of territorial reorganization which took place in the Toluca Valley between the end of the 18th and the beginning of the 19th century, based on the study of elementary schools. he study aims to shed light on the administration and the resource management of these institutions in two contrasting eras: on the one hand, what happened in the periods of viceroyalty and independence, and on the other hand, the events that occurred in the jurisdictions of which the city of Toluca was a part (irst the marquis period and followed by the state period). his was contrast compared to other towns in the valley. he documentary sources which have served as background support to this study come from national archives, as well as from a dozen of municipal historical archives which keep a rich heritage of the period in question. As a corollary, we suggest variations and continuities, among them processes of territorial reorganization.